Systemic blood pressure in Peruvian Andean populations: a study - Segura Vega, Luis (2021)
Introduction: The diagnosis of arterial hypertension in adults is based on figures above 140/90 mmHg, conventional values ​​of normality, universal, for any age or sex. There are a large number of comparative studies between chronic residents of high altitude and those at sea level, with significantly differentiable results, as a consequence of their successful adaptation to the chronic hypoxic-hypobaric environment at high altitude. For the correct diagnosis and treatment of their diseases, it is necessary to establish the ranges of normality that correspond to them. Objective: To determine the normal blood pressure pattern of these permanent inhabitants of high altitudes. Method: Cross-sectional, epidemiological cohort study, one cohort represented by the coastal population and another cohort represented by the Andean population. Results: Of the 12,448 persons selected on the coast, 51% were women and 49% men, with ages ranging from 18 to 97 years, and a mean age of 43.8 years. In the Andean highlands, of the 6,253 people selected, 48.7% were men and 51.3% were women, with an average age of 41.8 years. On the coast, of the 6,195 selected, 49.3% were male and 50.7% female, with an average age of 48.7%. On the coast, the cut-off value for systolic blood pressure of 140 mmHg corresponded to the 91.9th percentile, taking into account the estimated mean age of 48.7 years; therefore, the cut-off-point for the inhabitant of the Peruvian highlands, systolic blood pressure would be 134 mmHg. Meanwhile, the cutoff value for diastolic blood pressure of 90 mmHg on the coast corresponds to the 86.2 percentile, taking into account the estimated mean age of 48.6 years; the cut-off point for diastolic blood pressure for the inhabitant of the highlands would be 89.1 mmHg. Conclusion: The present study finds that 134/89 mmHg is the limiting pattern of normal systolic and diastolic blood pressure in the adult inhabitant of the Andean highlands.